2022
DOI: 10.1136/jitc-2021-003883
|View full text |Cite
|
Sign up to set email alerts
|

Unique characteristics of tertiary lymphoid structures in kidney clear cell carcinoma: prognostic outcome and comparison with bladder cancer

Abstract: BackgroundThe aims of this study were (1) to clarify the impact of tertiary lymphoid structure (TLS) status on the outcome and immunogenomic profile of human clear cell renal cell carcinoma (ccRCC) and (2) to determine phenotypic differences in TLSs between different types of genitourinary cancer, that is, urinary ccRCC and bladder cancer.MethodsWe performed a quantitative immunohistological analysis of ccRCC tissue microarrays and conducted integrated genome mutation analysis by next-generation sequencing and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 40 publications
0
24
2
Order By: Relevance
“…However, Masuda et al. 31 recently showed that the maturity, spatial distribution and prognostic impact of TLSs were significantly different between the two types of genitourinary cancers, clear‐cell renal cell cancer and bladder cancer, which suggests that the effects of TLSs on tumours were tumour type specific. We found that only the presence of mature TLSs predicted better survival in ESCCs, which is similar to pancreatic cancers, 32 lung squamous cell carcinomas 33 and colorectal cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Masuda et al. 31 recently showed that the maturity, spatial distribution and prognostic impact of TLSs were significantly different between the two types of genitourinary cancers, clear‐cell renal cell cancer and bladder cancer, which suggests that the effects of TLSs on tumours were tumour type specific. We found that only the presence of mature TLSs predicted better survival in ESCCs, which is similar to pancreatic cancers, 32 lung squamous cell carcinomas 33 and colorectal cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of TLSs correlated with patient survival in endometrial cancers, 27 head and neck squamous cell carcinomas, 28 metastatic melanomas 29 and non-functional pancreatic neuroendocrine tumours, 30 regardless of their maturation status. However, Masuda et al 31 recently showed that the maturity, spatial distribution and prognostic impact of TLSs were significantly different between the two types of genitourinary cancers, clear-cell renal cell cancer and bladder cancer, which suggests that the effects of TLSs on tumours were tumour type specific. We found that only the presence of mature TLSs predicted better survival in ESCCs, which is similar to pancreatic cancers, 32 lung squamous cell carcinomas 33 and colorectal cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The maturation stage of TLSs in cancer varies from B cell aggregates to organized structures with germinal centres 42,96 . In untreated lung 40,41 , colorectal 83 and bladder cancer 100 , mature, germinal centre-positive TLSs are a positive prognosticator of survival, whereas immature TLSs have either no association or a weak association with survival. In hepatocellular carcinoma, mature TLSs correlate with improved survival [101][102][103] , whereas immature TLSs serve as survival niches for tumour progenitor cells and confer a worse prognosis 104 .…”
Section: Cancermentioning
confidence: 99%
“…In lung squamous cell carcinoma, TLS are the independent prognostic marker and their development can be affected by chemotherapy and steroids ( 91 ). Interestingly, between different types of genitourinary cancer, one study showed that TLS displayed a distinct status in terms of the clinical outcome and immunogenomic profile ( 92 ). Researchers showed that the TLS detected in RCC cohort were less mature, contributing to poor outcomes, while in bladder cancer cohort, TLS were more mature with GC structures and associated with better outcomes ( 92 ).…”
Section: Indications Of Tls and Immunotherapymentioning
confidence: 99%
“…Interestingly, between different types of genitourinary cancer, one study showed that TLS displayed a distinct status in terms of the clinical outcome and immunogenomic profile ( 92 ). Researchers showed that the TLS detected in RCC cohort were less mature, contributing to poor outcomes, while in bladder cancer cohort, TLS were more mature with GC structures and associated with better outcomes ( 92 ). Another study certificated that in three gradual levels of immune infiltration of ccRCC clusters, higher abundance of T cells and TLS, suggesting an immune-enriched TME, was related to poor clinical outcome ( 93 ).…”
Section: Indications Of Tls and Immunotherapymentioning
confidence: 99%